ENHANCING UNIVERSITY STUDENTS' INTERPERSONAL COMPETENCE THROUGH KIPAS COUNSELING GROUNDED IN BUGIS PAPPASENG - Sudirman, M Yunus; Amirah Budi, Nurwafiqaf; Astin, Nur (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
This study aims to develop and evaluate the KIPAS Counseling Model rooted in Bugis pappaseng to improve the interpersonal competence of university students. This model was designed using the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) framework. Data were collected through questionnaires, expert validation, pretest–posttest design, observation, and focus group discussions, with 60 students and five experts (counseling lecturers and cultural experts) participating. The results showed significant improvements in five dimensions of interpersonal competence: effective communication, positive interaction, understanding self and others, appreciation and empathy, and social solidarity. The overall average score increased from 61.2 (moderate category) to 81.3 (high category), with a t-value = 14.27, p < 0.001, and a large effect size (Cohen's d = 1.25). Qualitative data supported these results, where students reported increased self-confidence, deeper empathy, and stronger social ties after participating in culture-based counseling. Practically, the KIPAS Model offers a counseling framework that is contextual, sustainable, and relevant to students' needs, while revitalizing the value of local wisdom. Academically, this research contributes to the development of cross-cultural counseling literature and demonstrates that local wisdom can be the foundation for modern counseling innovation. The KIPAS Model also has the potential to be replicated and adapted to other cultural contexts in Indonesia, thereby strengthening multicultural education in higher education.